Telling Tales: A Survey of Narratological Approaches to Music - Millard, Russell (Current Musicology, 2018)
Of the various hermeneutic approaches to the study of music developed in the last half century or so, narratological analysis has gone further than many in navigating a path that draws on both cultural and structural contexts. This overview of the development of narrative theory in music charts the course of three “waves” of narratological engagement with music: 1) the scholars of the 1980s, such as Anthony Newcomb, Susan McClary, and Patrick McCreless, whose work focused on narrative in instrumental tonal music; 2) a period of critical reappraisal of musical narrative in the 1990s by writers such as Jean-Jacques Nattiez and Carolyn Abbate; 3) the opening up of narrative theory to broader musical repertories—e.g. film and popular music—with scholars such as Nicholas Reyland. Important strands of narrative thinking are highlighted, demonstrating the significance of balancing structural and “humanistic” approaches to the study of music through narrative, encouraging close theoretical links between cultural and analytical readings.